Annual plant reviews, Volume 13: Plastids - Møller, Simon Geir (Blackwell, 2012)
Reviews plastids, which are essential plant organelles, vital for life on earth. This volume is suitable for researchers and professionals working in plant physiology, cell biology, genetics, molecular biology, biochemistry and agriculture.